DEVELOPMENT OF COMPOSITE REINFORCEMENTS AND CONCRETE DEFORMATIONS IN BASALT REINFORCED CONCRETE BEAMS - Solijonov Foziljon Sodiqjon ugli (Journals Park Publishing, 2023)
This article describes the analysis of the results of the research carried out on the study of the work of composite reinforced elements, which are widely used in the restoration of concrete structures in the buildings and structures currently being built in the Republic of Uzbekistan and in foreign countries. The article includes the types of composite reinforcements, the physical and mechanical properties of composite reinforcements, and the proposed practical recommendations for ensuring their strength, uniformity and seam resistance.
Keywords: cоmpоsite, basalt, cоncrete, flexibility, strength, messura, pоlymer, deformation, compression, stretch.